Interviewing for solutions - De Jong, Peter, 1945 -; Berg, Insoo Kim; Brooks/Cole (Pacific Grove, CA : Brooks/Cole, 2002)
A practical, skills-based video that includes six segments, comprising 22 video clips, illustrating the solutions-focused conversations discussed in De Jong and Berg's text and accompanying workbook
VHS
Keywords: Social case book; Interviewing; Short-term counseling; Solution-focused therapy